Initiation of oxidative degradation in polypropylene reactor powder produced by Ziegler-Natta catalyst. (March 2017) - Tobita, Taira; Chammingkwan, Patchanee; Terano, Minoru; Taniike, Toshiaki
Abstract: The oxidative degradation of polypropylene reactor powder was studied to clarify the origin of initial radicals that trigger auto-oxidation. Polymerization conditions were found to have direct impacts on the stability of as-synthesized polymer irrespective of catalyst residues and polymer structures. Polypropylene produced under a higher yield condition exhibited a shorter lifetime with a larger amount of oxidative products after air exposure, suggesting the presence of a larger amount of initial radicals. The addition of a nitroxide radical trapping agent drastically enhanced the stability of as-synthesized polymer by passivating the initially formed radicals. Different experimentation approaches revealed that initial radicals are plausibly formed in polymerization.